"Diminishing returns" in the scaling of leaf area vs. dry mass in Wuyi Mountain bamboos, Southeast China. Issue 7 (12th July 2017) - Sun, Jun; Fan, Ruirui; Niklas, Karl J.; Zhong, Quanlin; Yang, Fuchun; Li, Man; Chen, Xiaoping; Sun, Mengke; Cheng, Dongliang
Abstract : PREMISE OF STUDY: Leaf area and dry mass are crucial for plant metabolic performance. The "diminishing returns" hypothesis predicts that leaf area will scale less than one with respect to leaf dry mass, indicating that the cost of light interception increases with leaf area. However, it remains unclear whether and how this scaling relationship varies among species growing in different environments. METHODS: More than 2000 measurements from five bamboo species adapted to high and low light and growing at different elevations in Wuyi Mountains, Southeast China, were used to explore how the leaf area vs. dry mass scaling relationship was affected by light and elevation. KEY RESULTS: The data indicate that (1) the normalization constants for leaf area vs. dry mass were positively but not significantly correlated with increasing leaf size and that (2) the scaling exponents remained numerically invariant among all five bamboo species, with a common slope of 0.85. Standardized major axis (SMA) analyses and comparisons of 95% confidence intervals also showed that the numerical values of the scaling exponents did not differ regardless of elevation and were similar between shaded and unshaded adapted species, whereas the numerical values of the normalization constants increased with decreasing light. CONCLUSIONS: The data collected for all five bamboo species are consistent with the "diminishing returns" hypothesis, i.e., the scaling exponents governing the leaf area vs. dry mass scaling relationship are less than one within and across species and are insensitive to light conditions or elevation.